1953
DOI: 10.1098/rspa.1953.0007
|View full text |Cite
|
Sign up to set email alerts
|

The D-D cross-section and angular distribution between 55 and 430 keV

Abstract: The cross-section and angular distributions of protons from the D-D reaction using thin gas targets have been measured from 55 to 430 keV. The results have been expressed in the form σ θ = ( σ /4 π (1+⅓ A +1/5 B )) (1+ A cos 2 θ + B cos 4 θ). The variation of the total cross-section … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1954
1954
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In Fig. 4 the same quantity is shown for the 2H(d, p)-reaction, containing the data of Davenport et al [29], Theus et al [34], Booth et al [24] and Tai et al [36], who all used thin gas targets in their experiments. Fig.…”
Section: (0 E) =-~ (Bo (E) + Bj (E) L2 (Cos 9)) (22)mentioning
confidence: 72%
“…In Fig. 4 the same quantity is shown for the 2H(d, p)-reaction, containing the data of Davenport et al [29], Theus et al [34], Booth et al [24] and Tai et al [36], who all used thin gas targets in their experiments. Fig.…”
Section: (0 E) =-~ (Bo (E) + Bj (E) L2 (Cos 9)) (22)mentioning
confidence: 72%
“…We updated for each reaction the data sets from direct measurement to be compared with the THM one, to better estimate the impact of the indirect result. For the pt channel we have chosen data reported in Greife et al (1995), Krauss et al (1987), McNeill and Keyser (1951), Schulte et al (1972), Brown and Jarmie (1990), Ganeev et al (1957), Arnold et al (1954), Raiola et al (2002), Booth et al (1956), Davenport et al (1953), Von Engel and Goodyear (1961), Cook and Smith (1953), Moffatt et al (1952), Tie-Shan et al (2007), and Leonard et al (2006). The data set in Greife et al (1995) shows an enhanced S-factor at very low energy values due to the electron screening effect.…”
Section: H(dp) 3 Hmentioning
confidence: 99%
“…S uch a plot is often called a Gamow plot and is frequently used in the analysis of the low energy data. Looking at the experimental results from three groups [2][3][4] in the energy region of about 8 to 100 k ev (center of mass), Brennan [5] has indicated that the d ata might suggest an increase in B of eq (1) with energy. Brennan calculated the D-D reaction cross section using a low energy approximation [6] to the small absorption method of Ostrofsky, Breit, and John son [7].…”
Section: (In= (A /E) Exp (-Be-i)mentioning
confidence: 99%
“…We see that the correction term can vary quite a bit depending on the value of Uo. Analyzing the available data [2][3][4], Brennan [5] decided on a value of Uo in the vicinity of 9 MeV.…”
mentioning
confidence: 99%